Penyimpangan Prinsip Sopan Santun Materi Anekdot Pada Buku Teks Bahasa Indonesia Kelas X Sma Kurikulum 2013 - Widyawati, Noviana; , Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
The curriculum is an important part in education. The curriculum is able provide the foundation and serve as guidelines for the development of learners' ability optimally as requirements and needs of the students, parents, and society. The paradigm of curriculum 2013 has set texs-Based Language learning including anecdotes text. The purpose of this study are (1) to describe the realization of the maxim form of deviations principle of politeness contained in the text of anecdotes. (2) describe the factors that cause deviations principle of politeness contained in the text of anecdotes. This research is a qualitative research. The method of collecting data in this study is 'simak' method, tapping techniques and note taking. The object of this research is anecdotes text that deviate the principle of politeness. The result based on Indonesian language book of SMA class X curriculum 2013 showed some of result as follows (1) the utterances in anecdotes text contained deviations such as tact maxim, dan (2) it was found the factors affecting the deviation principle of politeness including criticized directly by using swear words, emotional impulse of speakers, deliberately accused the opponents speakers, protective of his/her own opinions, and deliberately discredit opponents speaker. Key words: principle of politeness, deviations, anecdotes text